Research on Enterprise Value Management of Emerging Industries in the Age of Artificial Intelligence. Issue 1 (March 2021) - Ye, Jingyi
Abstract: The arrival of the era of artificial intelligence is both an opportunity and a challenge, and the main research of artificial intelligence enterprises, belongs to the emerging industry, it is very different from the traditional industry. How to measure its enterprise value, has become a controversial issue. This article from the artificial intelligence industry analysis, combined with its particularity, through comparative analysis of all kinds of enterprise valuation method, choose the real options method to measure the value of the company, applying Schwartz - Moon model combined with Monte Carlo simulation to evaluate the enterprise value of Robots(300024), find out the reasonable artificial intelligence class enterprise value evaluation model, and gives the corresponding Suggestions, helps to guide the orderly development of the industry, promote the development of artificial intelligence and innovation.